Environmental Education (EE) from an Islamic Perspective - Al-Hadabi, Abdulsalam Sulaiman Dawood (Journal of Amran University, 2022)
Due to human-being's action, environment is being rapidly changing. Human being's action is greatly affecting the environment in several ways that are unsustainable, undesirable, and unpredictable. Such misuse is the main cause for environmental pollution (EP) which is a key reason that our home (i.e. earth) is dying day-by-day. Therefore, the effect of the transition from present day patterns of unsustainable development is an issue that should be argued by all individuals, parents, teachers, schools, universities, etc. Yet, it is indispensable that everyone must be aware of environment impacts, as an ultimate goal for environmental education (EE). This research aimed to develop a model for EE to use as a framework of EE in the Islamic countries, such as Yemen. To this end, the researcher analyzed the available related literature as well as the Qur'anic verses and the tradition of Mohammed peace be upon him (PBUH). An Islamic Model for EE, as a result of analyzing the related literature, Qur’anic verses, and the traditions of Prophet, Mohammad, PBUH, was presented in this research.